Perceptions de la population vis-à-vis des banques participatives : Cas du Maroc: Population's perceptions towards participatory banks: Case of Morocco - M’HARZI ALAOUI, Ibtissam (African Scientific Journal, 2020)
Today, the existence of participatory banks is an observed phenomenon in several countries, even those with a large Muslim minority, for instance Europe and the United States. Thus, over the years, the participatory banking sector has been projected in a sphere of a very enviable rate growth Despite the enthusiasm aroused by participatory finance at the international level, the Moroccan context is still slow to fully adopt it and the integration potential of this banks has proved to be limited for the time being. The objective of this study is to shed light on the factors explaining this shyness breakthrough toward Islamic finance, namely consumer perception. Data collection was based on a questionnaire administered to 537 respondents. Then, the detailed analysis and interpretations concerning the data collected for the study was discussed in detail using the IBM SPSS software. The results obtained show that more than a half of those respondents (nearly 58%) have a real intention to join participatory banks. However, a large proportion (almost 41%) prefer to keep their conventional accounts. These findings push us to wonder about the factors explaining these obtained results. Résumé : L'existence de banques participative représente un phénomène observé dans de nombreux pays aujourd’hui, y compris dans des pays à forte minorité musulmane, notamment l'Europe et les États-Unis. Ainsi, au fil des années, le secteur des banques participative s'est projeté dans une sphère où le taux de croissance se révèle très enviable. En dépit de l'engouement suscité par la finance participative au niveau international, le contexte marocain tarde encore à l'adopter pleinement et le potentiel d'intégration des banques participative s'avère pour l'heure limité. L’objectif de cette étude vise à mettre en lumière sur les facteurs expliquant cette timide percée de la finance islamique, notamment la perception des consommateurs. La collecte des données a été faite sur la base d’un questionnaire administré à de 537 enquêtés. Ensuite, l'analyse détaillée et l'interprétation des données recueillies pour l'étude ont été discutées en détail à l'aide de l'outils statistique d'IBM SPSS. Les résultats obtenus montrent que la moitié des interrogés (près de 58%) témoignent d’une réelle intention d’ouvrir un compte dans une banque participative. Cependant, une très grande proportion (près de 41%) préfère garder leurs comptes conventionnels. Ce constat nous amène à̀ nous interroger sur les facteurs expliquant ces résultats obtenus. Mots clés : finance participative, banque participative, perception des consommateurs.